ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PERMINTAAN BARANG IMPOR PADA E-COMMERCE SHOPEE DI KOTA DENPASAR - Supriyanah, Supriyanah; Ayuningsasi, Anak Agung Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 13 No 6 (2024): Vol.13.No.6. JUNI.2024 [393-451], 2024)
Imports are part of international trade that can be carried out by individuals, businesses, and local governments. This research aims to analyze the simultaneous and partial influence of free shipping, e-wallet, and price variations on demand for imported products on Shopee e-commerce in Denpasar City. The population of this research is the population of productive age in Denpasar City, namely 474,504 people with a sample size of 100 people. Sampling was carried out using the purposive sampling method. The data analysis technique used in this research is multiple linear regression analysis. The research results show that free shipping, e-wallet, and price variations simultaneously have a significant influence on the demand for imported products on Shopee e-commerce in Denpasar City. Free shipping and e-wallets partially have a positive and significant impact on demand for goods on Shopee e-commerce in Denpasar City, while price variations have a negative and significant impact. This research theoretically contributes to the development of studies related to international trade theory, while empirically it can contribute to considering variables that influence the demand for imported goods in Denpasar City. keyword : free shipping promotion, e-wallet, prices, e-commerce, and demand for imported goods